Solvability of inhomogeneous boundary-value problems for fourth-order differential equations - Avci, H.; Tunç, E. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Some new oscillation criteria are established for the nonlinear damped differential equation (r(t)k_1 (x, x’))’ + p (t) k_2 (x, x’) x’ + q (t) f (x (t)) = 0,t ≥ t_0. The results obtained extend and improve some existing results in the literature.